Model Kepemimpinan Visioner Kyai dalam Mengembangkan Pendidikan Pesantren - Imaduddin, Imaduddin (UII Darullughah Waddawah Pasuruan, 2024)
This study investigates how Kyai visionary leadership contributes to the development of training education in Indonesia. This research reveals how kyai, as a visionary leader, can lead the coaches in facing the challenges and changes of the modern world while preserving traditional Islamic values. The research uses a qualitative approach that involves in-depth interviews, observations, and document analysis. Kyai plays an important role as a spiritual and moral guide, creating a supportive and inclusive environment for academic and personal growth. The study emphasizes the importance of visionary leadership in curriculum development, promoting a learning culture that fits students' needs, and how it affects student performance and overall training effectiveness. The study also found the benefits of Kyai visionary leadership in improving the quality of education and building the creative character of the centre. The results provide practical insights for educators and leaders in the Islamic education system, especially the practitioners. They also offer advice to encourage dynamic and supportive future leadership practices.